2021
DOI: 10.3390/e23111377
|View full text |Cite
|
Sign up to set email alerts
|

Many-Body Localization and the Emergence of Quantum Darwinism

Abstract: Quantum Darwinism (QD) is the process responsible for the proliferation of redundant information in the environment of a quantum system that is being decohered. This enables independent observers to access separate environmental fragments and reach consensus about the system’s state. In this work, we study the effect of disorder in the emergence of QD and find that a highly disordered environment is greatly beneficial for it. By introducing the notion of lack of redundancy to quantify objectivity, we show that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Several different versions of such models were studied as examples of quantum Darwinism ([ 131 , 143 , 144 , 145 , 146 , 149 , 151 , 152 , 153 , 154 , 155 , 156 , 157 ]). In this section, we focus on the steady state situation when the evolution results, at long times, in a PIP that is largely time-independent.…”
Section: Quantum Darwinismmentioning
confidence: 99%
“…Several different versions of such models were studied as examples of quantum Darwinism ([ 131 , 143 , 144 , 145 , 146 , 149 , 151 , 152 , 153 , 154 , 155 , 156 , 157 ]). In this section, we focus on the steady state situation when the evolution results, at long times, in a PIP that is largely time-independent.…”
Section: Quantum Darwinismmentioning
confidence: 99%
“…Let us first study the establishment and spread of correlations in the considered scenarios. As discussed in detail in many publications [ 6 , 23 , 24 , 25 , 40 , 41 , 42 , 43 , 44 ], this feature might have an impact on the notion of objectivity for a quantum state, in the spirit of so-called quantum Darwinism [ 3 ] (see, for example, ref. [ 7 ] for a recent review and references therein).…”
Section: Spreading Of Correlationsmentioning
confidence: 99%
“…Quantum Darwinism can be hindered by numerous factors, such as non-Markovianity [32,[58][59][60][61][62][63][64], non-ideal environments [33,34], initial system-environment correlations [32,35], environment-environment interactions [23,24,32,62,65], etc. It was shown that environment-environment interactions can lead to thermalisation at the detriment of objectivity in [23,24], but it is still open whether the other factors would lead to similar behaviour.…”
Section: Setting Coexistencementioning
confidence: 99%
“…However, information and correlations have an associated energy [21,22], and naively, this information should not survive under the process of thermalisation. For example, in the model analysed by Riedel et al [23], some level of objectivity emerges at finite time, before equilibration sets in; in the model analysed by Mirkin and Wisniacki [24], tuning certain parameters produces either objectivity or thermalisation, but not both.…”
Section: Introductionmentioning
confidence: 99%